In‐depth characterization of Trichoderma reesei cellobiohydrolase TrCel7A produced in Nicotiana benthamiana reveals limitations of cellulase production in plants by host‐specific post‐translational modifications. Issue 3 (17th August 2019) - van Eerde, André; Várnai, Anikó; Jameson, John Kristian; Paruch, Lisa; Moen, Anders; Anonsen, Jan Haug; Chylenski, Piotr; Steen, Hege Særvold; Heldal, Inger; Bock, Ralph; Eijsink, Vincent G. H.; Liu‐Clarke, Jihong
Summary: Sustainable production of biofuels from lignocellulose feedstocks depends on cheap enzymes for degradation of such biomass. Plants offer a safe and cost‐effective production platform for biopharmaceuticals, vaccines and industrial enzymes boosting biomass conversion to biofuels. Production of intact and functional protein is a prerequisite for large‐scale protein production, and extensive host‐specific post‐translational modifications (PTMs) often affect the catalytic properties and stability of recombinant enzymes. Here we investigated the impact of plant PTMs on enzyme performance and stability of the major cellobiohydrolase Tr Cel7A from Trichoderma reesei, an industrially relevant enzyme. Tr Cel7A was produced in Nicotiana benthamiana using a vacuum‐based transient expression technology, and this recombinant enzyme ( Tr Cel7A rec ) was compared with the native fungal enzyme ( Tr Cel7A nat ) in terms of PTMs and catalytic activity on commercial and industrial substrates. We show that the N‐terminal glutamate of Tr Cel7A rec was correctly processed by N. benthamiana to a pyroglutamate, critical for protein structure, while the linker region of Tr Cel7A rec was vulnerable to proteolytic digestion during protein production due to the absence of O ‐mannosylation in the plant host as compared with the native protein. In general, the purified full‐length Tr Cel7A rec had 25% lower catalytic activity than Tr Cel7A nat and impaired substrate‐binding properties, which can be attributed to larger N ‐glycans and lack of O ‐glycans in Tr Cel7A rec . All in all, our study reveals that the glycosylation machinery of N. benthamiana needs tailoring to optimize the production of efficient cellulases.